Practical aspects of creation of magnetic oils - Соловьев, С.Н.; Трофимова, Е.В. (Problems of Tribology, 2014)
Common problems on optimization of compositions of magnetic oils for greasing of mechanical systems are formulated. Recommendations about creation of magnetic oils taking into account quantitative and high-quality selection of the disperse environment, a disperse phase and SAS are provided